In vivo roles of integrins during leukocyte development and traffic: insights from the analysis of mice chimeric for alpha 5, alpha v, and alpha 4 integrins. - Arroyo,AG; Taverna,D; Whittaker,CA; Strauch,UG; Bader,BL; Rayburn,H; Crowley,D; Parker,CM; Hynes,RO (J Immunol, 2000)
Mice chimeric for integrins alpha(5), alpha(V), or alpha(4) were used to dissect the in vivo roles of these adhesion receptors during leukocyte development and traffic. No major defects were observed in the development of lymphocytes, monocytes, or granulocytes or in the traffic of lymphocytes to different lymphoid organs in the absence of alpha(5) or alpha(V) integrins. However, in agreement with previous reports, the absence of alpha(4) integrins produced major defects in development of lymphoid and myeloid lineages and a specific defect in homing of lymphocytes to Peyer's patches. In contrast, the alpha(4) integrin subunit is not essential for localization of T lymphocytes into intraepithelial and lamina propria compartments in the gut, whereas one of the partners of alpha(4), the beta(7) chain, has been shown to be essential. However, alpha(4)-deficient T lymphocytes cannot migrate properly during the inflammatory response induced by thioglycolate injection into the peritoneum. Finally, in vitro proliferation and activation of lymphocytes deficient for alpha(5), alpha(V), or alpha(4) integrins upon stimulation with different stimuli were similar to those seen in controls. These results show that integrins play distinct roles during in vivo leukocyte development and traffic.